Reverse hybrid jig separation efficiency estimation of floating plastics using apparent specific gravity and concentration criterion - Phengsaart, Theerayut; Manositchaikul, Chaiwat; Srichonphaisarn, Palot; Juntarasakul, Onchanok; Maneeintr, Kreangkrai; Jeon, Sanghee; Park, Ilhwan; Tabelin, Carlito Baltazar; Hiroyoshi, Naoki; Ito, Mayumi (Frontiers in Chemistry, 2022)
We developed a technique called the reverse hybrid jig, an advanced physical separation technique that combines the principles of jig and flotation to separate floating plastics. This technique is a promising green technology that is more economical and environmentally friendly compared with the conventional flotation. Although the applicability of this technique to separate PP/PE have been reported, the index to illustrate the possibility of separation for the reverse hybrid jig is still not available. In this study, a reverse apparent concentration criterion (CCRA) is proposed to estimate reverse hybrid jig separation efficiency. This modified concentration criterion can be calculated using the specific gravity (SG) of particle with attached bubbles called the apparent specific gravity (SGA). To determine the volume of attached bubbles on plastic surfaces under water pulsation, a laser-assisted apparatus was used under various conditions, including plastic type, air flow rate, dosage, and type of wetting agent. The results of attached bubble volume measurements were used to calculate the SGA and CCRA. The estimated values were then compared with the results of reverse hybrid jig separation. It was found that higher CCRA resulted in better separation efficiency. In addition, an empirical linear equation for estimating the reverse hybrid jig separation efficiency is proposed.